Information technology. International standardized profile RA. Relaying the connectionless-mode network service. Definition of profile RA51.1111, relaying the connectionless-mode network service between CSMA/CD LAN subnetworks and PSDNs using virtual calls over a PSTN leased line permanent access Part 8, (15th January 1995) - British Standards Institution,
No abstract available